Analisis Klaim Al-Ghazali tentang Tindakan Allah dalam 'Al-Iqtisad fi al-I'tiqad': Kajian terhadap Bantahan atas Pemikiran Mu'tazilah - Haya, Haya; Hosaini, Hosaini; Afrita , Juwika; Bustomi, Muhamad Yazid (Universitas Bondowoso, 2023)
Imam Al-Ghazali, whose full name is Abu Hamid bin Muhammad bin Ahmad Al-Ghazali, is a prominent figure in Islamic philosophy and theology who was born in 450 AH near Thus, Khurasan, Islamic Republic of Iraq. His important work,